The secret science project that almost ate the school - Sierra, Judy.; Gammell, Stephen (New York : Simon & Schuster Books for Young Readers, 2006)
A girl sends off for "Professor Swami's Super Slime" to use as her science fair project and then has to cope with the funny disaster that follows.
"A Paula Wiseman book.".
Library Media Connection starred.
School Library Journal.
Wilson's Children.
3.3
K-3
Keywords: Schools -- Juvenile fiction; Science projects -- Juvenile fiction; Humorous stories; Schools -- Fiction; Science projects -- Fiction; Stories in rhyme; Humorous fiction; School stories; Science projects -- Fiction; Stories in rhyme; Humorous fiction